2022
DOI: 10.3389/fgene.2021.750947
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of mRNAs, lncRNAs, and Proteins, and Their Relationship With Sheep Fecundity

Abstract: The exploration of multiple birth-related genes has always been a significant focus in sheep breeding. This study aimed to find more genes and proteins related to the litter size in sheep. Ovarian specimens of Small Tail Han sheep (multiple births) and Xinji Fine Wool sheep (singleton) were collected during the natural estrus cycle. Transcriptome and proteome of ovarian specimens were analyzed. The transcriptome results showed that “steroid hormone biosynthesis” and “ovarian steroidogenesis” were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In comparison, Dolang sheep, which are widely bred in the south Xinjiang region of China [38], have strong adaptability but low fecundity compared to Small Tail Han sheep [39][40][41][42], with an average litter size of 1.4 [43,44]. Multiple studies have been conducted by researchers used RNA sequencing to analyze the gene expression patterns in the ovaries of Small Tail Han sheep during the follicular and luteal phases of the estrous cycle [45][46][47]. These studies have identified several differentially expressed genes that are involved in follicular development, oocyte maturation, and luteinization, all of which are important for fertility and concluded that Small Tail Han sheep have a unique molecular mechanism for regulating ovarian function, which may contribute to their high fecundity.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, Dolang sheep, which are widely bred in the south Xinjiang region of China [38], have strong adaptability but low fecundity compared to Small Tail Han sheep [39][40][41][42], with an average litter size of 1.4 [43,44]. Multiple studies have been conducted by researchers used RNA sequencing to analyze the gene expression patterns in the ovaries of Small Tail Han sheep during the follicular and luteal phases of the estrous cycle [45][46][47]. These studies have identified several differentially expressed genes that are involved in follicular development, oocyte maturation, and luteinization, all of which are important for fertility and concluded that Small Tail Han sheep have a unique molecular mechanism for regulating ovarian function, which may contribute to their high fecundity.…”
Section: Introductionmentioning
confidence: 99%
“…A negative effect of dioxin on the expression of the HSD17B1 gene has been described, thereby causing the inhibition of steroidogenesis [94]. In addition, this gene has been identified as a marker of steroidogenesis in ovine granulosa cells, thus affecting fecundity in this species [95]. A downregulation of FST (follistatin) was revealed in the current study, which could positively affect porcine GCs' proliferation and estrogen secretion [96].…”
Section: Discussionmentioning
confidence: 50%
“…Phospholipase A2 group IVB ( PLA2G4B ) gene encodes a member of the cytosolic phospholipase A2 protein family and has a role in calcium ion binding and phospholipase activity. This gene has been identified as one of the important genes in interaction networks in sheep fertility [ 115 ]. Cytochrome P450 family 2 subfamily S member 1 ( CYP2S1 ) encodes a member of the cytochrome P450 superfamily of enzymes.…”
Section: Discussionmentioning
confidence: 99%